Komunitas perokok di kedai kopi: tantangan untuk promosi kesehatan - Dedy Setiawan; Supriyati Supriyati; Atik Tri Ratnawati (Berita Kedokteran Masyarakat (BKM), 2018)
The intention of behavior to come to the coffee shop in Bengkalis societyPurpose: Smoking while drinking coffee at the coffee shop every morning are the behavior of society in Bengkalis. Those habits facilitate a person to interact with one another. Tar and nicotine in cigarette and caffeine in coffee conformity impair health, especially in the cardiovascular system. A qualitative study has to be done, to explore the intention of people to come to the coffee shop.Methods: Descriptive explorative research with a qualitative approach. Subjects were 5 visitors who smoke and drink coffee, 2 visitors who don’t smoke and don’t drink coffee, 2 coffee shop owners and a coffee shop worker in Bengkalis. Samples are taken by purposive sampling, the research did until getting saturated data. Data collection by participant observation and in-depth interview. Data analysis did with content analysis.Results: This research showed the intention of people to come to the coffee shops: having breakfast (drink, eat, smoke), meeting (chat, discuss, lobby, campaign), and looking for a chance (information, relation, promotion). That intention is influenced by attitude, subjective norm, and perceived control. Attitudes: come to the coffee shop are a habit, important, and necessity, visitors support this habit; subjective norm: perception about the importance of social interaction to get information and relations; and perceived control behavior: no wife support, advice from doctor, and prohibition of civil servant at coffee shop in working time.Conclusion: The intention is influenced by attitude, perception about social encouragement, and perceived control behavior to come to the coffee shop. The intervention of health promotion is needed with emphasizing factors that influence visitors’ intention to come to the coffee shop.